The Mitotic Phosphorylation Cycle of the Cis-Golgi Matrix Protein Gm130 - Lowe, Martin (The Rockefeller University Press, 2000)
The cis-Golgi matrix protein GM130 is phosphorylated in mitosis on serine 25. Phosphorylation inhibits binding to p115, a vesicle-tethering protein, and has been implicated as an important step in the mitotic Golgi fragmentation process. We have generated an antibody that specifically recognizes GM130 phosphorylated on serine 25, and used this antibody to study the temporal regulation of phosphorylation in vivo. GM130 is phosphorylated in prophase as the Golgi complex starts to break down, and remains phosphorylated during further breakdown and partitioning of the Golgi fragments in metaphase and anaphase. In telophase, GM130 is dephosphorylated as the Golgi fragments start to reassemble. The timing of phosphorylation and dephosphorylation correlates with the dissociation and reassociation of p115 with Golgi membranes. GM130 phosphorylation and p115 dissociation appear specific to mitosis, since they are not induced by several drugs that trigger nonmitotic Golgi fragmentation. The phosphatase responsible for dephosphorylation of mitotic GM130 was identified as PP2A. The active species was identified as heterotrimeric phosphatase containing the Bα regulatory subunit, suggesting a role for this isoform in the reassembly of mitotic Golgi membranes at the end of mitosis.